O39-2 The avoidable future burden of copd due to occupational respirable crystalline silica exposure in the EU. (1st September 2016) - Tan, Emma; Fishwick, David; Pronk, Anjoeka; Drossard, Claudia; Lüdeke, Andreas; Bochmann, Frank; Schlünssen, Vivi; Hansen, Jitka; Sigsgaard, Torben; Østrem, Ragnhild; Eduard, Wijnand; Bugge, Merete; et al.
Abstract : Objectives: Studies have shown that exposure to respirable crystalline silica (RCS) can lead to an increased risk of chronic obstructive pulmonary disease (COPD). Approximately five million EU workers are thought to be currently exposed to RCS in the EU, four million in construction work. The aim of this study was to evaluate the potential impact of intervention scenarios, designed to reduce RCS exposure within the EU, on the future burden of COPD in exposed workers. Methods: A microsimulation model was developed to simulate workers, incorporating the effects of RCS exposure and smoking on the development of COPD. A baseline scenario was carried out, simulating workers with the highest median RCS exposures based on previous measures in these sectors; including construction (0.09 mg/m³; 4.1 million workers) and manufacturing of mineral products (0.045 mg/m³; 535, 000 workers), and assuming future exposures remain at current levels. Various intervention scenarios were then simulated; one modelled a 6% decline per year in median exposures from current levels; another modelled an increase in compliance with a 0.1 mg/m³ exposure limit (the proposed Binding Occupational Limit Value across the EU). Results: Under the intervention scenario where median exposures decline by 6% annually, approximately 630, 000 new cases of COPD are expected to be prevented (of a total of 2.8 million under the baseline scenario) over the next 25 years. An alternative scenario where 90% compliance with a 0.1 mg/m³ limit is achieved results in approximately 980, 000 cases prevented. In both scenarios, the greatest impact would be in countries with the largest construction sectors. Conclusion: For reductions in RCS exposure by increasing compliance or reducing median levels, the model predicts a substantial reduction in future burden of COPD, mainly within construction; however there remains uncertainty in the characterisation of exposures and the effects of exposure on lung function.